2018
DOI: 10.1002/chem.201800467
|View full text |Cite
|
Sign up to set email alerts
|

Large Oblate Hemispheroidal Ruthenium Particles Supported on Calcium Amide as Efficient Catalysts for Ammonia Decomposition

Abstract: Ammonia decomposition is an important technology for extracting hydrogen from ammonia toward the realization of a hydrogen economy. Herein, it is reported that large oblate hemispheroidal Ru particles on Ca(NH ) function as efficient catalysts for ammonia decomposition. The turnover frequency of Ru/Ca(NH ) increased by two orders of magnitude when the Ru particle size was increased from 1.5 to 8.4 nm. More than 90 % ammonia decomposition was achieved over Ru/Ca(NH ) with large oblate hemispheroidal Ru particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…[1][2][3] Among the available catalysts for ammonia decomposition under mild conditions, Pt has been identified as one of the most promising candidates. 4,5 The polycrystalline surfaces of Pt, including (100), (111), and (533), have been employed as active substrates for ammonia decomposition to produce N 2 and H 2 . [6][7][8][9][10] However, the Pt catalysts for ammonia decomposition, including the use of doped Pt, 11 are to the best of our knowledge still not sufficiently effective at low temperatures (e.g., <350°C) and thus are not economically viable for large-scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Among the available catalysts for ammonia decomposition under mild conditions, Pt has been identified as one of the most promising candidates. 4,5 The polycrystalline surfaces of Pt, including (100), (111), and (533), have been employed as active substrates for ammonia decomposition to produce N 2 and H 2 . [6][7][8][9][10] However, the Pt catalysts for ammonia decomposition, including the use of doped Pt, 11 are to the best of our knowledge still not sufficiently effective at low temperatures (e.g., <350°C) and thus are not economically viable for large-scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…Such an increase in oxidation state has been reported for other TM-amide-based catalysts, and was attributed to charge transfer between Ru and KNH 2 to form Ru–N bonds (or ternary nitride species) and thereby catalyzing the decomposition of NH 3 . 38 For example, it has been reported that NH 3 decomposition over Li 2 NH doped with 3d transition metals (nitrides) such as Fe, Co, and MnN involve two steps: 28 (1) the reaction of Li 2 NH and transition metal (nitride) to form ternary nitride and H 2 ; (2) the ammoniation of the ternary nitride to Li 2 NH, transition metal (nitride), and N 2 . Ternary nitride is not expected to be formed in systems such as Ru–Li 2 NH, MnN–NaNH 2 , and MnN–KNH 2 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, we developed a composite catalyst system of Li 2 NH-3 d transition metal or transition metal nitride (TM(N)), in which Li 2 NH synergized with 3 d TM(N) (from Ti to Cu) leading to universal high catalytic activities towards NH 3 decomposition [54,55] . In addition to 3 d metals, Ru was also found to synergize with amides and imides of alkali and alkaline earth metals, such as LiNH 2 /Li 2 NH, Ca(NH 2 ) 2 and Ba(NH 2 ) 2 , and these composites exhibited remarkably high activities towards ammonia decomposition [56][57][58] . An efficient ammonia decomposition catalyst may catalyze the reverse reaction, i.e., ammonia synthesis, as well.…”
Section: Thermocatalytic Ammonia Synthesismentioning
confidence: 99%